AUTOMATIC GALLON WATER SYSTEM MONITORING APPLY FUZZY LOGIC - Zulfahmi Syahputra; Muhammad Syahputra Novelan; Purwa Hasan Putra (INFOKUM, 2021)
A dispenser is a household appliance that is used by almost every Indonesian citizen, a dispenser is a household appliance that functions as a container for gallons of water to refill. Because water is a very promising need, the water refill gallon business is very rapidly developing, both water depot owners or consumers sometimes cannot know when the gallon water runs out unless they see it directly, sometimes due to dense activity so they cannot monitor repeatedly when the water is gallon. it ran out so research was carried out on the manufacture of automatic dispensers. To carry out the automation process, it is assisted by a microcontroller device called Wemos D1, besides that there are two sensors as sending messages, namely the ultrasonic sensor and the infrared tcrt 5500 sensor with the help of an Android-based application so that water notifications run out on the smartphone. In addition, to calculate the messages sent through the sensor, the fuzzy logic method is used. After testing in this study, the ultrasonic sensor sends a message for water conditions in gallons and has a vulnerable value (0 - 40) 0 is a full gallon and 40 is an exhausted gallon. While the infrared tcrt 5500 sensor sends a message for gallon conditions and has a vulnerable value (100-1000) 100 is the value of gallons installed (GTS) and 1000 is the value of gallons not installed (GTT), it can be concluded that the applied method can determine the water condition used up and the condition of the gallon that is not installed and the accuracy obtained is 98%.